2021
DOI: 10.1186/s12989-021-00434-x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and structural analysis of engineered stones and inorganic particles in silicotic nodules of exposed workers

Abstract: Background Engineered stone silicosis is an emerging disease in many countries worldwide produced by the inhalation of respirable dust of engineered stone. This silicosis has a high incidence among young workers, with a short latency period and greater aggressiveness than silicosis caused by natural materials. Although the silica content is very high and this is the key factor, it has been postulated that other constituents in engineered stones can influence the aggressiveness of the disease. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
1
17
1
1
Order By: Relevance
“…In contrast, a study of sandblasters found that silicosis was linked to both exposure concentration and duration 32. Our findings suggest that other exposure factors besides work tenure alone, including RCS concentration, particle size and mineralogical characteristics, and chemical composition of particulate matter retained in workers’ lungs, may be important in risk for disease from ES dust 33 34. Pavan et al hypothesise that enhanced free radical production from ES dust containing greater quantities of transition metal ions may augment the pulmonary fibrogenic response compared with quartz alone 35.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast, a study of sandblasters found that silicosis was linked to both exposure concentration and duration 32. Our findings suggest that other exposure factors besides work tenure alone, including RCS concentration, particle size and mineralogical characteristics, and chemical composition of particulate matter retained in workers’ lungs, may be important in risk for disease from ES dust 33 34. Pavan et al hypothesise that enhanced free radical production from ES dust containing greater quantities of transition metal ions may augment the pulmonary fibrogenic response compared with quartz alone 35.…”
Section: Discussioncontrasting
confidence: 62%
“… 32 Our findings suggest that other exposure factors besides work tenure alone, including RCS concentration, particle size and mineralogical characteristics, and chemical composition of particulate matter retained in workers’ lungs, may be important in risk for disease from ES dust. 33 34 Pavan et al hypothesise that enhanced free radical production from ES dust containing greater quantities of transition metal ions may augment the pulmonary fibrogenic response compared with quartz alone. 35 Investigation of ES dust mineralogy using animal models and in situ techniques may provide additional insights into disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Phthalic anhydride and styrene were two of the most common compounds, together making up 31–88% of the total organic composition of the emissions by PY-GC-MS. Similar organic species were observed when León-Jiménez et al (2021) and Hall et al (2021) pyrolyzed small pieces of engineered stone samples. Given the role of styrene and phthalic anhydride in the manufacture of polymer and epoxy resins, their presence in the resin-containing engineered stones is perhaps not surprising ( WHO, 1999 ; Tustin et al , 2022 ).…”
Section: Discussionsupporting
confidence: 62%
“…However, little information is available on the organic nature of the dust emitted from engineered stone fabrication work, which could be contributing to the aetiology of lung disease in this occupational group. There appear to be two published works which have explored the organic composition of bulk engineered stone material, but the speciation of organics released during active machining, which could have health implications, is relatively unexplored ( Hall et al , 2021 ; León-Jiménez et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Engineered Stone is a composite material fabricated with finely crushed natural rocks with high content in silica, assembled with polymeric resins as a binder, and in general, adding different pigments like metals. Usually, ES is composed of 10–15% of resins and the rest is silica, cristobalite or quartz in different concentrations 3 . Reports of a significant number of affected workers initially came from Israel 4 and Spain 5 .…”
Section: Introductionmentioning
confidence: 99%